Identifying Gojek Problems Using Servqual And Kano Methods - Febriana, Dyah Ayu; binsyeh, muhammad idrus; Rizky DF3, Achmad; Oktavia A, Wanda; Rizky, Eka Nur; Hariastuti, Ni Luh Putu (Universitas Insan Cendekia Mandiri, 2025)
This study aims to analyze service quality issues faced by Gojek, an Indonesian digital platform, using the SERVQUAL and Kano methods. SERVQUAL measures the gap between user expectations and perceptions across five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data were collected from 78 Gojek users. Findings show that all 19 service attributes exhibit negative gaps, indicating customer expectations exceed perceived performance. Key attributes with the largest gaps, such as driver timeliness and responsiveness, are classified as Must-be or One-dimensional, critical for customer satisfaction. Some features were identified as Attractive or Indifferent, suggesting areas for strategic service improvements. This research offers a framework for Gojek to enhance service quality and maintain competitive advantage in a saturated digital market.